Fundamentals of Entrepreneurship (ENT300) : Business opportunity Hani’s Cupcake / Hashmaimah Abdullah … [et al.] - Abdullah, Hashmaimah; Mad Suliman, Mohd Azam; Appolonius, Norbert; Ismail, Nurul Izzah (2019)
Sam's Centre is one of the attractions of student as its provided variety brand of stationeries. Other than that, the residents of Desa llmu also used Sam's Centre services to complete their daily task. Besides, Sam's Centre also known as one of the leading companies and it has been established long time ago to serve the community. Plus, the company offering the wholesale price for all items in their branch. The main reason for the company stays and expand their branch in Kota Samarahan is because they are targeting universities students as their main incomes. Other than that, they also get demands for customers to expand their services especially printing services in the company. The case study that has been evaluated show that Sam's Centre has a very high opportunity to b expand for future as its help students as well as the community to ease their task and helps them to get high quality materials with affordable price.